Towards a framework for predicting whole life-cycle cost for long-term digital preservation - Badawy, Mohamed; Sanya, Isaac; Shehab, Essam; Baguley, Paul (Cranfield University Press, 2013)
Estimating the costs for the whole lifecycle of long-term digital preservation (LTDP) activities ena-bles decision makers to choose carefully what data to preserve, duration of preservation and type of preservation techniques best applied for their information. To address this need, a framework is de-veloped to generate a cost model that will estimate costs for long-term digital preservation activities using storage in the cloud and taking into consideration the impact of mitigating uncertainties, espe-cially obsolescence issues on future costs. This cost estimating framework is part of the European pro-ject entitled ‘Enabling kNowledge Sustainability Usability and Recovery for Economic value’ which aims to provide a total long-term digital preservation solution for companies and public sector organi-sations interested in keeping their digital information alive for the long-term within the healthcare, fi-nancial and the clinical trials business sectors.
Keywords: Digital Preservation; Cloud Computing; Uncertainties; Obsolescence; Cost Estimation; Whole Lifecycle Cost; ENSURE